From the subtropics to the central equatorial Pacific Ocean: Neodymium isotopic composition and rare earth element concentration variations. Issue 2 (4th February 2013) - Grenier, Mélanie; Jeandel, Catherine; Lacan, François; Vance, Derek; Venchiarutti, Célia; Cros, Alexandre; Cravatte, Sophie
Abstract : [1] Neodymium isotopic compositions ( ε Nd ) and rare earth element (REE) concentrations were measured for filtered surface to deep waters (112 samples) in the Southern Tropical Pacific. The relatively detailed picture of these tracer distributions allowed us to refine the areas where oceanic ε Nd variations occur. ε Nd values increase for most of the water masses flowing from Samoa to the Solomon Sea and in the Papua New Guinea (PNG) area, as already observed. Furthermore, water masses arriving from the eastern equatorial Pacific (200–550 m depth) also revealed radiogenic values, possibly acquired in the vicinity of the South American coasts and Galapagos Islands. These ε Nd variations affect the whole water column. The most likely process causing such variations is "boundary exchange" between the numerous radiogenic slopes/margins located in this area and seawater flowing past. Dissolution of atmospheric deposition and/or diffuse streaming of volcanic ash are also suggested to explain the radiogenic ε Nd observed at the surface in the PNG area. Interestingly, a positive europium (Eu) anomaly characterizes the normalized REE patterns of most of the studied water masses. This anomaly is consistent with the REE patterns of sediment and rock samples that are potential sources for the local waters. Such consistency reinforces the hypothesis that lithogenic sources play a major role in the oceanic REE budget, thanks to "boundary exchange." The data set presented here is a good basis for further sampling that will be realized in the framework of the ongoing GEOTRACES program (www.geotraces.org). Key Points: ENd values increase for most of the water masses flowing from Samoa to the PNG ENd variations affect the whole water column, suggesting boundary exchange The positive europium anomaly reinforces the boundary exchange hypothesis